Paul's Arguments as Evidence of the Christianity from which he Diverged - Smith, Morton (Harvard theological review, 1986)
While the topic of this paper is familiar, I believe that one source of information has been generally neglected: the arguments that Paul does not use. Since Bishop Stendahl has done so much to illuminate Paul's words, it seems appropriate to dedicate to him this brief sketch of things to be learned from Paul's silence.